Clinical-histopathological concordance in head and neck lesions. - Sahily Espino Otero; Julio Romero Rodrígez; Yordany Boza Mejías; Odalys Acevedo Sierra; Iván Quintana Hijano; Phede Selme (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2009)
Background: Clinical-histopathological data contributes to a better diagnosis, assessment and treatment of head and neck lesions. Objective: To determine clinical-histopathological correlation of head and neck lesions. Methods: a descriptive, retrospective, observational study was developed in a series of cases (360 patients) to determine the clinical diagnostic scope in relation to the histopathological techniques used in the Maxillary Surgery Service of "Gustavo Aldereguía Lima" hospital between June 2006 and 2007. Required data was taken from clinical histories and records from Pathological Anatomy, which were transferred to a form design for that purpose. Results: The age group of 0-19 years had the higher concordance among the studied groups (72,4%). 59, 7% of the studied cases had clinical-histopathological concordance, mainly in extra-oral lesions (60, 4%) particularly in the vermilion border (82, 4 %) and among the intra-oral the most common were those in the vestibular duct (100%). The most important lesions where clinical diagnosis did not coincide with histopathological diagnosis were fibroma with 23 in the intra-oral and warts and a total of 34 in extra-oral, followed by basal carcinomas. Conclusions: There is a significant correlation between clinical and histopathological diagnosis, suggesting high attention quality and correct application of the clinical method as central element in patients' management.